Dynamics of Jovian and Saturnian stream particles - Hsu, Hsiang-Wen (2010)
Stream particles are nanometer-sized dust particles ejected with speeds greater than 100km/s from the Jovian and Saturnian system. Due to their tiny size, the dynamics of the charged grains is dominated by electromagnetic forces. The strong correlation between the stream particle flux and the strength of the interplanetary magnetic field (IMF) was observed first by the dust detectors on the Ulysses and Galileo spacecrafts. The Cosmic Dust Analyser (CDA) onboard the Cassini spacecraft offers the unique opportunity achieve a deeper understanding of the stream particle phenomenon due to the detectors̉ improved sensitivity and its capability to determine the particles' composition. Furthermore, CDA is so far the only detector which observed stream particles from both source planets. The direct comparison between the properties of grains from different source planets provide deep insights into the physics of the dust-magnetosphere interaction. Because the observations of Jovian stream particles by three spacecrafts covers a very long time span, also the long term evolution of the stream particle flux can be studied ...
Online publiziert: 2010
Keywords: Hochschulschrift; Planetarer Ring; Magnetosphäre; Interplanetarer Staub; Saturn